2021
DOI: 10.1093/jas/skab072
|View full text |Cite
|
Sign up to set email alerts
|

Glycine ameliorates mitochondrial dysfunction caused by ABT-199 in porcine oocytes

Abstract: Mitochondria play an important role in controlling oocyte developmental competence. Our previous studies showed that glycine can regulate mitochondrial function and improve oocyte maturation in vitro. However, the mechanisms by which glycine affects mitochondrial function during oocyte maturation in vitro have not been fully investigated. In this study, we induced a mitochondrial damage model in oocytes with the Bcl-2-specific antagonist ABT-199. We investigated whether glycine could reverse the mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…Gly is the main component of GSH. Our previous study also verified that Gly treatment had a beneficial effect on in vitro oocyte maturation and blastocyst development by decreasing ROS levels to reduce apoptosis (Qu et al, 2002;Yu et al, 2021). In this study, Gly treatment reversed the decrease in GSH levels and the increase in ROS levels induced by TG.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Gly is the main component of GSH. Our previous study also verified that Gly treatment had a beneficial effect on in vitro oocyte maturation and blastocyst development by decreasing ROS levels to reduce apoptosis (Qu et al, 2002;Yu et al, 2021). In this study, Gly treatment reversed the decrease in GSH levels and the increase in ROS levels induced by TG.…”
Section: Discussionsupporting
confidence: 82%
“…Our previous studies showed that 6 mM Gly treatment has a beneficial effect on oocyte IVM and subsequent blastocyst development after parthenogenetic activation (PA) by decreasing ROS levels and increasing mitochondrial function (mitochondrial ΔΨ m, ATP concentration) to reduce apoptosis and regulate gene expression related to development (FGFR2 and Hsfl) and apoptosis (Bax and Bcl2). Furthermore, we also proved that Gly could improve oocyte IVM by regulating the [Ca 2+ ] i to enhance mitochondrial function ( Yu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations